Institutionalised management of food security: FCI$1 (Bs role in safe storage, distribution and transportation of food grains s - Meena, Ashok K.K. and Kumar, Chandrasen (Kurukshetra: A Journal on Rural Development)
India rune the world$1 (Bs largest food security management system, not only in terms of number of people who benefit directly but also in terms of volume of operations and vastness of the related supply chain. While safe storage of food is the most important requirement to run this complex system, transpiration from spurious regions to deficit regions and eventual distribution among a large number of beneficiaries and Institutions are equally important features. The nodal Institution managing this herculean task is food corporation of India undertaking. This article brings out the contemporary status of the food storage infrastructure required for food security management, along with the related supply chain of transportation and distributing of food grains across the country- Reproduced s